Pseudomonas juntendi sp. nov., isolated from patients in Japan and Myanmar. Issue 11 (1st August 2019) - Tohya, Mari; Watanabe, Shin; Teramoto, Kanae; Shimojima, Masahiro; Tada, Tatsuya; Kuwahara-Arai, Kyoko; War, May Wint; Mya, San; Tin, Htay Htay; Kirikae, Teruo
Abstract : A Gram-negative, aerobic, rod-shaped, non-spore-forming bacterium, designated as strain BML3 T, was isolated from a sputum sample of a hospital patient in Japan. Strain BML3 T grew at temperatures from 4 to 40 °C, in 1.0–7.0 % (w/v) NaCl and at pH 6.0–9.0. Results of phylogenetic analysis based on the sequences of housekeeping genes, including the 16S rRNA gene and rpoB, rpoD and gyrB, showed that strain BML3 T was part of the Pseudomonas putida group and located close to Pseudomonas asiatica, Pseudomonas monteilii and P. putida . Whole-genome comparisons, using average nucleotide identity and digital DNA–DNA hybridization, confirmed strain BML3 T to be a distinct species among the P. putida group. Phenotypic characterization tests demonstrated that the utilization of phenylmercuric acetate could distinguish this strain from other closed species of the P. putida group. Based on genetic and phenotypic evidence, strain BML3 T should be classified as a novel species, for which the name Pseudomonas juntendi sp. nov. is proposed. The type strain is BML3 T (=DSM 109244 T, =JCM 33395 T ), with a DNA G+C content of 62.66 mol %.